It had to be you [large type] - Brazier, Eliza Jane (Thorndike Press large print top shelf., 2024)
"When Eva and Jonathan hook up on the sleeper train from Florence to Paris, they think they'll never see each other again. Which is too bad, because neither has ever felt a spark like this for another person. But love isn't on the agenda in their line of work. Six months later, they run into each other in the Hall of Mirrors in Versailles. This encounter is not by chance, because Eva has been hired to kill Jonathan. She's a contract killer, but what she doesn't know is that he is too. Their meeting kicks off a high-stakes adventure across Western Europe. As the two get closer to completing their assignments, it becomes clear that they are also being hunted by something even more dangerous than love"--